Timor-Leste Social Assistance : Public Expenditure and Program Performance Report - World Bank (Washington, DC, 2013)
The Democratic Republic of Timor-Leste is a young, post-conflict nation endowed with significant oil revenues. Timor-Leste has one of the highest birth rates in the world (2.41 percent population growth) with over 44 percent of the population below 15 years of age (Timor-Leste Census, 2010). Since the 2006 crisis, the Government of Timor-Leste has shown a clear commitment to social assistance. Globally, poverty persistence is closely related to major life-cycle disadvantages resulting in low human capital outcomes, and yet large-scale poverty remains unaddressed by current social protection efforts. This expenditure review and performance evaluation report is part of the technical assistance provided to Timor-Leste's Ministry of Social Solidarity (MSS) in response to the lack of any national level evaluation of the safety nets system since its inception. To that end, this study seeks to assess the social assistance policy, as well as the performance of the main MSS social assistance programs. More specifically, the aims are to: (1) determine whether existing programs are efficient, effective and sufficient in addressing main vulnerabilities; (2) assess the adequacy and composition of the allocation of financial resources for delivery of government social assistance; (3) review operational and administrative issues; and (4) make recommendations for improving the delivery of social safety nets. Some of the questions that this report seeks to answer include: what are the main risks facing the vulnerable groups in Timor-Leste?; what types of programs are in place to address those risks?; is the range of programs and their financial allocations appropriate for the country's needs?; is the institutional arrangement adequate?; are these programs effective and reaching the intended beneficiaries?; and are they implemented cost-effectively? The report is organized as follows: chapter one gives context, purpose and conceptual framework. Chapter two describes the attributes of the poorest 40 percent and the main vulnerabilities and risks that low-income families in Timor-Leste face. Chapter three provides a historical overview of the social assistance policy and programs that emerged after the 2006-2007 conflict. A summary of levels and trends in aggregate public expenditure on safety nets, composition of spending as well as program-specific budget analysis is presented in chapter four. Chapter five assesses performance of the safety nets by analyzing coverage, targeting effectiveness, and generosity. Chapter six examines impact and targeting efficiency using simulation techniques. Chapter seven assesses implementation capacity, and business processes, and in particular, the following: ID systems, enrollment, payments arrangements and monitoring and evaluation. Chapter eight concludes with implications for social response and policy considerations.